2022
DOI: 10.1186/s12934-022-01836-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of gut microbiota in healthy and diarrheic yaks

Abstract: Background Yak (Bos grunniens) mainly inhabiting Tibet Plateau, displayed a high incidence of diarrhea due to harsh living environment and nutritional deficit. Gut microbial community has been reported to be closely related to many diseases including diabetes, obesity and inflammatory bowel disease, but information regarding diarrheic influence on gut microbiota in yaks remains scarce. Here, this study was performed to investigate the gut bacterial and fungal alternations of diarrheic yaks. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 67 publications
4
19
0
Order By: Relevance
“…At the phylum level, our research results show that Firmicutes and Bacteroides are the two main groups, followed by Spirochaetes, Tenericutes, Verrucomimicrobia and Proteobacteria. This is consistent with the research results of Liu et al [25] and Wen et al [23]. It is worth noting that the addition of 6% and 9% Scutellaria baicalensis Georgi stems and leaves signi cantly reduced the ratio of Firmicutes/ Bacteroides.…”
Section: Discussionsupporting
confidence: 92%
“…At the phylum level, our research results show that Firmicutes and Bacteroides are the two main groups, followed by Spirochaetes, Tenericutes, Verrucomimicrobia and Proteobacteria. This is consistent with the research results of Liu et al [25] and Wen et al [23]. It is worth noting that the addition of 6% and 9% Scutellaria baicalensis Georgi stems and leaves signi cantly reduced the ratio of Firmicutes/ Bacteroides.…”
Section: Discussionsupporting
confidence: 92%
“…The intestinal tissue injury is mediated through the administration of the antioxidants ( Dashdorj et al, 2013 ; Aziz et al, 2021 ; Hassan et al, 2021 ; Liu et al, 2021 ; Murtaza et al, 2021 ). Oxidative agents of SOD, T-AOC, GSH-Px, and MDA are commonly known important enzymes related to oxidative stress, which may cause intestinal damage ( Mehmood et al, 2019 ; Liu J. et al, 2022 ). In mice serums, no obvious difference was found in GSH-px and SOD between the control group and LPS-induced groups, respectively, while a prominently higher level of MDA ( p < 0.01) was detected in group L; however, there was a significant decrease in MDA ( p < 0.01) levels in sodium acetate/sodium butyrate supplemented groups D, B, and A, respectively ( Figure 3 ), suggesting that sodium acetate/sodium butyrate improves intestinal oxidative damage by reducing MDA contents.…”
Section: Discussionmentioning
confidence: 99%
“…Despite measures such as improved hygiene and scientific feeding management with the use of extensive drugs, this disease, i.e., diarrhea, remains serious ( Li et al, 2022 ). The imbalance in gut microbiota was commonly recognized as the primary cause of diarrhea ( Schmoeller et al, 2021 ), and many studies found changed intestine microbiota in diarrhea of cattle ( Chuang et al, 2022 ; Coelho et al, 2022 ; Li et al, 2022 ; Liu J. et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Animals of various species need to evolve different intestinal flora structures to adapt to their habitats, and diet characteristics, etc. ( Liu et al, 2021 , 2022 ). For example, herbivores have a higher intestinal flora structure to digest cellulose and realize energy conversion ( Dong et al, 2020 ; Yang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%